The dark side of screens: Exploring impairment with the iRAT framework - Memes, Mucho; Lusterfuck, Carlsen; Eatheater, Daniele (Annals of Mathematics and Physics, 2024)
This paper introduces the iRAT model, an extension of the existing RAT framework, to comprehensively evaluate the integration of digital media in educational settings. While the traditional RAT framework focuses on Replacement, Amplification, and Transformation, the iRAT model includes a fourth category: Impairment. This new category addresses the potential negative impacts of digital media use, such as unnecessary app usage, distractions from learning objectives, lack of pedagogical integration, and resource wastage. The study employs a mixed-methods approach, including participatory observation, lesson plan evaluation, expert think-aloud protocols, and AI-driven scenario identification, to validate the iRAT model. Findings highlight the importance of considering both positive and negative aspects of digital media integration, suggesting that future research should adopt the iRAT framework for a balanced evaluation. This study closes a significant research gap and challenges the overly optimistic view of digital media in education, advocating for a more critical perspective.